2021
DOI: 10.3390/f12111609
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Environmental Performance of Wood for a Second-Generation Biorefinery

Abstract: The current global climate change, the 2030 Agenda, and the planetary boundaries have driven new development strategies, such as the circular economy, bioeconomy, and biorefineries. In this framework, this study analyzes the potential availability and sustainability of the wood supply chain for a small-scale biorefinery aiming at producing 280–300 L of bioethanol per ton of dry biomass, consuming 30,000 t of dry biomass per year harvested in a 50 km radius. This wood production goal was assessed from Eucalyptu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Uruguay is characterized by the use of forest residues, due to the large number of hectares with trees to deforest. However, in some researches, it was found that the utilization of RLB is being chosen; for example, Rachid-Casnati et al ( 2021 ) established the possibility of implementing a biorefinery, in which between 280 and 300 L of ethanol/t of Eucalyptus biomass ( Eucalyptus grandis ) would be obtained. Other authors, such as Guigou et al ( 2019 ) performed an intensive pre-treatment of eucalyptus sawdust: some samples were initially treated with autohydrolysis at 170 °C and others with mechanical refining at 3000 rpm followed by Kraft pulping at 155 °C (3.4% alkaline loading).…”
Section: Introductionmentioning
confidence: 99%
“…Uruguay is characterized by the use of forest residues, due to the large number of hectares with trees to deforest. However, in some researches, it was found that the utilization of RLB is being chosen; for example, Rachid-Casnati et al ( 2021 ) established the possibility of implementing a biorefinery, in which between 280 and 300 L of ethanol/t of Eucalyptus biomass ( Eucalyptus grandis ) would be obtained. Other authors, such as Guigou et al ( 2019 ) performed an intensive pre-treatment of eucalyptus sawdust: some samples were initially treated with autohydrolysis at 170 °C and others with mechanical refining at 3000 rpm followed by Kraft pulping at 155 °C (3.4% alkaline loading).…”
Section: Introductionmentioning
confidence: 99%